A case study on overtime and its impacts on employees job satisfaction - KRISHNAMOORTHY, D.; ARAVINDAN.S (The journal of contemporary issues in business and government, 2020)
India became the fourth largest auto market in 2019 displacing Germany with about 3.99 million units sold in the passenger and commercial vehicles categories. As the industry grows employment and pressure on employees too grows. This article investigates the influence of overtime on employee’s job satisfaction. It establishes the importance of impact of job overtime on employees, increases work load and creates work family conflicts on them. This study is carried out to analyze the factors influencing job satisfaction, to study the factors that leads to work family conflict and to study the effect of work family conflict on job satisfaction